Pengaruh Pemberian IAA pada Pembibitan Setek Vanili (Vanila planifolia) yang diperkaya Bakteri Pelarut Fosfat dan Bakteri Pelarut Kalium - Kusbianto, Dwi Erwin; Emiyati, Sri; Setiawati, Tri Candra; Subroto, Gatot; Rosyady, Mohammad Ghufron (Jurnal Agro Industri Perkebunan, 2022)
Propagation of vanilla plants is generally using vegetative methods like cuttings. The use of external growth regulators can support the growth of nurseries. Phosphate solubilising bacteria and potassium solubilising bacteria as plant growth promoting rhizobacteria are producing microbial IAA. This study used auxin in synthetic IAA combined with IAA microbes from phosphate solubilising bacteria and potassium solubilising bacteria. This study aimed to determine the effectiveness of each microbe at each dose of synthetic IAA that was applied. The study was conducted from November 2021-April 2022 in the Biological Soil Laboratory and Greenhouse University of Jember. The research uses a randomised block design with three replications with the factorial arrangement. The first factor was organic matter which was enriched with bacterial isolate (B0 = control, B1 = BPF isolate, and B2 = BPK isolate). The second factor was concentration of IAA (A0 = 0 mg.l-1, A1 = 100 mg.l-1, and A2 = 200 mg.l-1). The data were analysed by ANOVA and further tested with Duncan Multiple Range Test (DMRT) with a 95% confidence level. The results showed that treatment of synthetic IAA affects the parameters of length and volume of adventitious roots, which are effective in helping to supply nutrients with the best treatment at a concentration of 200 ppm. Meanwhile, enrichment of media with isolates of phosphate solubilising bacteria and potassium solubilising bacteria gave a better effect than control on the observation of tendril length, number of leaves, number of adventitious roots and taproots, length of adventitious roots and taproots, the volume of adventitious roots and taproot, and fresh weight of vanilla seedlings.